دور أنشطة العلاقات العامة في إدارة الأزمات - دراسة ميدانية: بمؤسسة توزيع الكهرباء والغاز"سوق أهراس"- - ثلايجية أحلام; رمال بسمة (My University, 2021)
Summary : Our study on the role of custard cream in crisis management is a field study in an institution distribution of electricity and gas is a denial the mamaters repution ,specializing in communication and public barbershops. From the neighbor Al – Talayat ,"Thaligia Ahlam and Remal Basma " Where the subject of the reality Public relations activities in the institution and its role in crisis management and it know the reality of relations activities the general public in the institution is an area of research, we posed the following main question : What is the role of relationship activtise general crisis management ? The method that we used in our study is the sociah survey method . As for the study sample , where the research community consist of 10 banana workers , appointed on the ither side of the interests . As for most of the results that we reached through our study. As for the majority of the results that we reached through our study, they are: - The absence of specialists in communication and public relations who ensure the development and follow-up of communication activities in the institution. 1- The organization practices to a large extent the planning activity, by studying all the steps it takes, and where the practice of this activity intensifies, especially when it falls into a crisis. 2- The Sonelgaz Foundation practiced research activity while it was in the crisis, but that practice was in a random way by collecting information about the crisis. 3- The institution used field research to gather information to find out the causes of the crisis. 4- Communication strategies in crisis management at the Electricity and Gas Distribution Corporation are unknown to the respondents, what we might include within the strategy of secrecy that takes forms of ignoring the crisis. 5- The method used, whether in the face of crises, is the method of tactics and not the strategy, where the necessary plans and procedures are developed in due time without prior preparation. 6- - The General Directorate represents the active party in dealing with the crisis in the institution as it is a source of authority and enjoys centrality in decision-making in addition to organizing guidance and evaluation processes and all actions to be taken to deal with the crisis. ------------------------------- ملخص: دراستنا حول دور كريمة الكاسترد في إدارة الأزمات هي دراسة ميدانية في مؤسسة توزيع الكهرباء والغاز، وهي مؤسسة متخصصة في مجال الاتصالات وصالونات الحلاقة العامة. من جارة الطلائع، "أحلام وثلاجيا ورمال بسمة". حيثُ كان موضوع واقع أنشطة العلاقات العامة في المؤسسة ودورها في إدارة الأزمات، ومعرفة واقع أنشطة العلاقات العامة في المؤسسة، مجالًا للبحث، طرحنا السؤال الرئيسي التالي: ما دور العلاقات العامة في إدارة الأزمات العامة؟ منهج الدراسة و منهج المسح الاجتماعي. أما عينة الدراسة، فقد تكون مجتمع البحث من 10 عمال موز، تم تعيينهم من قبل جهات مختلفة. ومن أهم النتائج التي توصلنا إليها من خلال دراستنا: أما بالنسبة لغالبية النتائج التي توصلنا إليها من خلال دراستنا، فهي: - غياب متخصصين في الاتصال والعلاقات العامة يسهرون على تطوير ومتابعة أنشطة الاتصال في المؤسسة. 1- تمارس المؤسسة إلى حد كبير نشاط التخطيط، وذلك بدراسة جميع الخطوات التي تتخذها، حيث تشتد ممارسة هذا النشاط، خاصةً عند وقوعها في أزمة. 2- مارست مؤسسة سونلغاز نشاط البحث أثناء الأزمة، ولكن بطريقة عشوائية من خلال جمع المعلومات حول الأزمة. 3- لجأت المؤسسة إلى البحث الميداني لجمع المعلومات لمعرفة أسباب الأزمة. 4- استراتيجيات الاتصال في إدارة الأزمات بمؤسسة توزيع الكهرباء والغاز غير معروفة للمبحوثين، وهو ما يمكن أن ندرجه ضمن استراتيجية السرية التي تتخذ أشكال تجاهل الأزمة. 5- الأسلوب المتبع، سواء في مواجهة الأزمات، هو أسلوب التكتيك وليس الاستراتيجية، حيث يتم وضع الخطط والإجراءات اللازمة في الوقت المناسب دون إعداد مسبق. ٦- تمثل الإدارة العامة الطرف الفاعل في التعامل مع الأزمة في المؤسسة، فهي مصدر السلطات وتتمتع بمركزية اتخاذ القرار، بالإضافة إلى تنظيم عمليات التوجيه والتقييم وجميع الإجراءات الواجب اتخاذها للتعامل مع الأزمة.
Keywords: أنشطة العلاقات العامة، المؤسسة، إدارة الأزمات